Coproducing a physical activity referral scheme in Germany: A qualitative analysis of stakeholder experiences - Klamroth, Sarah; Mino, Eriselda; Naber, Inga; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (BMJ Open, 2024)
Objectives This study evaluated stakeholders' experiences of participating in a coproduction process to develop a physical activity referral scheme (PARS) in the German healthcare system. The focus was on examining facilitators and challenges, along with gathering insights on potential modifications to the joint development process, all from the viewpoint of stakeholders. Design This qualitative study employed one-to-one semi-structured interviews, and the findings were analysed using summarising qualitative content analysis. Setting The study focused on the German healthcare system. Participants Seven stakeholders from the coproduction process were purposefully selected for interviews using maximum variation sampling. The interviewees represented different sectors (physician associations, physical activity professionals' associations, health insurance companies and patient organisations), various positions within their organisations, and different levels of attendance during the coproduction process. Results In almost all interviews, the following factors were highlighted as facilitators of the development process: coproduction approach, process of coproduction, multi-sector stakeholder group, possibility of active participation, coordinating role of researchers, communication, atmosphere and interaction. In contrast, differences in roles and hierarchy, merging of different perspectives, clarification of intervention costs, and competition and conflicting interests were pointed out as challenges. Only a few suggestions regarding adaptations in terms of group composition and cooperation among stakeholders were mentioned. Conclusions Stakeholder experiences with the joint development process were predominantly positive, indicating that coproduction is a beneficial approach for the development of PARS intended for integration into healthcare systems. The effective management of power differences among stakeholders is intricately tied to the coproduction method; therefore, it should be selected carefully. The research team plays a pivotal role in coordinating and negotiating the process, and the team should be equipped with a diverse set of skills and knowledge, particularly to understand the intricacies of the healthcare system where the PARS is intended for implementation. Trial registration number NCT04947787.
CRIS-Team Scopus Importer:2024-05-31
Keywords: health services; patient participation; primary health care; qualitative research